Vitamin levels in a selected population in the Czech Republic - Pavlík, Vladimir; Fajfrova, Jana; Hlubik, Pavol; Drahokoupilova, Eva (Neuro endocrinology letters, 2010)
OBJECTIVES: The work objective was to monitor nutritional habits in the observed group of professional soldiers with the focus on eating food with the content of antioxidant carriers. Then to show present state of health and nutrition in the group on the basis of anthropometric measurements and biochemical examinations and finally to observe the level of antioxidant vitamins in the observed group of professional soldiers. METHODS: The group included 171 healthy individuals, 152 men and 19 women. Their average age was 34.2±7.9 years. The venous blood was taken for biochemical examinations in all individuals on a fast. Anthropometric measurements (weight, height, caliperation, waist circumferences), blood pressure and pulse were taken continually in all individuals. Simple questionnaires were administered to all participants for the complete evaluation of present health and for the registration of eating habits of the observed persons. RESULTS: The study results show that retinol and a-tocoferol levels in the observed group were within a normal range. The average concentration of vitamin C in this group was 54 mmol/l and reached nearly the values given in other European countries. But concentrations of β-caroten and lycopen in serum were up to 50% lower in comparison with concentrations in population in the countries of West Europe. Higher vitamin C and β caroten serum levels were found in individuals who respond in a questionnaire they eat fruit and vegetables or supplements of vitamin preparations every day. Statistically lower levels of vitamin C, β karoten and lycopen in the group of obese people (compared with the group of normal weight people) show decreased level of antioxidant protection of the organism and the risk of cardiovascular diseases. CONCLUSIONS: The results show that it is necessary to ensure optimal food not only with an energetic diet value but also with a proper input of antioxidant carriers in the form of fresh vegetables and fruit every day.
Keywords: karotenoidy; nutriční stav; Czech Republic; vitamin A; Diet; Military Personnel; Female; Humans; dospělí; Nutritional Status; Vitamin A; Male; ženské pohlaví; alfa-tokoferol; beta-karoten; Česká republika; zdravotnické přehledy; lidé; ozbrojené síly; beta Carotene; Carotenoids; Vitamins; Health Surveys; kyselina askorbová; dieta; Lycopene; mužské pohlaví; vitaminy; alpha-Tocopherol; Ascorbic Acid; Adult; lykopen; Health Status; zdravotní stav